Penguasaan Teknik Listrik Guru STM Negeri se-Sulawesi Selatan - Aminuddin Bakry; Awaluddin Tjalla; Saliruddin Saliruddin (Universitas Negeri Malang, 2016)
The expost facto study with a sample of 53 teachers of STM was conducted in South Sulawesi. It was shown that the competency of the teachers in content subject area is very low measured by the criterion reference test as well as by the norm reference test. Another finding revealed that the correlation between education and upgrading in content subject area and its mastery is insignificant. Furthermore, there is a significant negative between teaching experience and content subject mastery.